Cryogenic 3D printing of damage tolerant hierarchical porous ceramics - Zheng Zhu; Dandan Gao; Zhuo Huang; Wei Chang; Bin Wu; Kaihao Zhang; Minghan Sun; Hengxu Song; Robert O Ritchie; Tao Wang; Wei Huang; Huamin Zhou (International Journal of Extreme Manufacturing)
Fabricating damage tolerant porous ceramics with efficient energy absorption and impact-resistant capability has been a challenge because of the brittle nature of ceramic materials. In nature, mineralized tissues or organisms such as cuttlebones and diatoms have evolved with hierarchical porous structures to overcome this difficulty. A bioinspired design of ceramic lattice structure with pores at multiple length scales, ranging from few nanometers to hundreds of micrometers, is proposed in the present work. These ceramic lattices with hierarchical porous structures were successfully fabricated via 3D cryogenic printing. Under quasi-static compressions, the printed ceramic lattices showed unprecedented long plateau strain (∼60%) and a specific energy absorption of ∼10 kJ·kg ^‒1 with a porosity of ∼90%. The resulting energy absorption capability was comparable with most composites and metals, thus overcoming the brittle nature of traditional porous ceramics. This was attributed to the delayed destruction of the lattice structure, as well as the gradual collapse of pores at multiple length scales. Similar trends have also been observed under split Hopkinson pressure bar (SHPB) tests, indicating excellent energy absorption under high strain-rate impacts. The proposed 3D printing technique that produces hierarchical pores was also demonstrated to apply to other functional materials, such as silicon carbide, barium titanate, hydroxyapatite, and even titanium alloy, thus opening up new possibilities for fabricating bioinspired hierarchical porous structures.